PENGARUH MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR MATEMATIKA KELAS 3 SD NEGERI 2 LAIS - Kurnia Agustina; Destiniar; Eka Fitri Puspa Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This researcher aims to determine whether there is an effect after using snakes and ladders media in mathematics learning. The method used in this study is a quantitative method with data collection techniques in the form of tests, namely pretest and posttest. The subjects of this study were 30 students of grade III of SD N 2 Lais. This result is proven through the results of the Paired Samples t-test which shows a calculated t value of -6.886 with a degree of freedom (df) of 29 and a significance value (Sig. 2-tailed) of 0.000. Because the significance value is smaller than the α = 0.05 level, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. This means that there is a significant difference between the pretest and posttest scores, where the average posttest score is higher than the pretest. Thus, this study confirms that the use of snakes and ladders media contributes positively to improving the mathematics learning outcomes of grade III students of SD Negeri 2 Lais.